2021
DOI: 10.21203/rs.3.rs-19991/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Human Factors Intervention in a Hospital - Evaluating the Outcome of a TeamSTEPPS Program in a Surgical Ward

Abstract: Background: Patient safety in hospitals is being jeopardized, since too many patients experience adverse events. Most of these adverse events arise from human factors, such as inefficient teamwork and communication failures, and the incidence of adverse events is greatest in the surgical area. Previous research has shown the effect of team training on patient safety culture and on different areas of teamwork. Limited research has investigated teamwork in surgical wards. The aim of this study was to evaluate th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Several reviews have demonstrated an effect of training emergency teams such as trauma-resuscitation surgical theatre teams 2 32. Recently, this has been shown for ward teams, too 33 34. Significant differences in PSC were found after a 12-month controlled study in two hospitals of a team-training intervention that focused on human factors, social and cognitive skills 34…”
Section: Discussionmentioning
confidence: 99%
“…Several reviews have demonstrated an effect of training emergency teams such as trauma-resuscitation surgical theatre teams 2 32. Recently, this has been shown for ward teams, too 33 34. Significant differences in PSC were found after a 12-month controlled study in two hospitals of a team-training intervention that focused on human factors, social and cognitive skills 34…”
Section: Discussionmentioning
confidence: 99%
“…The tools included in the TeamSTEPPS ® were implemented gradually during the intervention, and the teamwork competencies improved among the staff and thus improved patient safety in the surgical ward (Aaberg et al, 2021). The intervention affected the behavior and communication of the staff in their daily clinical practice at a surgical ward by allowing them to obtain a greater awareness and knowledge of their teamwork skills.…”
Section: Discussionmentioning
confidence: 99%
“…Daily rounds also serve as a rich learning environment for nurses, medical students, and surgeons-in-training, providing them the opportunity to observe and discuss best practices in care and develop their own clinical and diagnostic skills. Because of these contributing factors, the risk of adverse events in surgical care is higher than the 10% rate seen in overall hospital admissions (Aaberg et al, 2021; de Vries et al, 2008). Interestingly, most surgical errors occur outside the operating room, with many resulting from breakdowns in communication and teamwork (Greenberg et al, 2007).…”
Section: Introductionmentioning
confidence: 99%